Effects of sucrose concentration, vitamins, light intensity and mineral components on growth of Hibiscus sagittifolius Kurz cultured in vitro - Thu Minh, Nguyen Le; Phuong Duyen, Nguyen Thuy; Tuyet Anh, Le Thi; Quynh, Nguyen Thi (Academia Journal of Biology, 2016)
Hibiscus sagittifolius Kurz is one herb plant with tuber roots used in traditional medicine thanks to numerous pharmaceutical properties, such as brain stimulus, vitality strengthening, anti-neurasthenia, etc. Seed germination rate of H. sagittifolius is very low in nature; therefore, aiming to create the large number of uniform, high quality plants, factors affecting the propagation process including effects of sugar concentration, vitamins, light intensity and culture mineral components were investigated. After 42 days of culture, in vitro leafy nodal cuttings of H. sagittifolius cultured photoautotrophically in polypropylene bags under high light intensity, 150 µmol m-2 s-1, photoperiod of 12 h d-1, room temperature at 25oC ± 2oC and relative humidity (RH) of 55% ± 5%, showed a better growth than that cultured photomixotrophically or photoautotrophically under low light intensity, 75 µmol m-2 s-1. On 6 different culture media (MS, 1/2 MS, 1/2 NH4, SH, B5, EN), in vitro leafy nodal cuttings of H. sagittifolius cultured photoautotrophically on SH medium had the greatest increased fresh weight (384.9 mg/plant), and their root growth conformed to their shoot growth better than those in other treatments on day 42. This study proved that H. sagittifolius plants had the best growth when cultured in vitro in polypropylene bags having two paper membranes, on SH mineral medium without sucrose and vitamins, under light intensity of 150 µmol m-2 s-1, photoperiod of 12 h d-1, room temperature at 25oC ± 2oC and RH of 55% ± 5%. Citation: Nguyen Le Thu Minh, Nguyen Thuy Phuong Duyen, Le Thi Tuyet Anh, Nguyen Thi Quynh, 2017. Effects of sucrose concentration, vitamins, light intensity and mineral components on growth of Hibiscus sagittifolius Kurz cultured in vitro. Tap chi Sinh hoc, 39(1): 86-95. DOI: 10.15625/0866-7160/v39n1.8468. *Corresponding author: qtnguyen_vn@yahoo.com. Received 6 July 2016, accepted 20 March 2017